(Re)conceptualizing institutional change in sport management contexts: the unintended consequences of sport organizations' everyday organizational life. Issue 2 (15th March 2019) - Fahlén, Josef; Stenling, Cecilia
ABSTRACT: Research question: The purpose of this paper is to construct empirically grounded concepts that can aid the explanation of processes of institutional change. This effort is guided by the observation that neither 'structure-centred' nor 'actor-centred' explanations of institutional change are equipped to provide a satisfactory explanation of one of organizational institutionalism's basic assumptions: that organizations are products of and produce their institutional contexts. Therefore, the focus is directed at practitioners' everyday struggle to accomplish their work, and institutional change is conceptualized as an unintended consequence of such mundane 'muddling through'. Research methods: The text is based on video recordings of board meetings in two sport clubs over one year. Data collection resulted in approximately 33 h of observation data from 17 board meetings. Results and findings: Analysis shows how sport club boards' interpretive processes of meaning making are instances of unintentional coproduction that plant seeds for institutional change. The creation of such seeds is the result of processes of problem–solution approximation and the use of proximal institutional raw material. This shows how sport organizations are crucial actors in the creation, modification, and transformation of the institutional arrangements prescribing appropriate organizational behaviour and enforcing patterns of interest and privilege. This analysis contributes knowledge on how sport organizations unintentionally coproduce increasing government reliance on sport organizations, professionalization, and commercialization. Implications: Such knowledge can make sport organizations and policy-makers aware of how unintentional coproduction might lead to the momentum of processes adverse to their needs and wishes.